The word became flesh - Erickson, Millard J. (Grand Rapids Baker Books House, 1991)
A respected author offers this detailed, well-documented exploration of the person of Christ that is accessible for laypersons and stimulating for academics. Top-notch reading.
Keywords: Jesus Christ -- Person and offices. Incarnation. Jesus Christ